Endocytic Trafficking at the Mature Podocyte Slit Diaphragm - Swiatecka-Urban, Agnieszka (Frontiers in Pediatrics, 2017)
Endocytic trafficking couples cell signaling with the cytoskeletal dynamics by organizing a cross-talk between protein networks in different subcellular compartments. Proteins residing in the plasma membrane are internalized and transported as cargo in endocytic vesicles (i.e. endocytosis). Subsequently, cargo proteins can be delivered to lysosomes for degradation or recycled back to the plasma membrane. The slit diaphragm is a modified tight junction connecting foot processes of the glomerular epithelial cells podocytes. Signaling at the slit diaphragm plays a critical role in the kidney while its dysfunction leads to glomerular protein loss (proteinuria) manifesting as nephrotic syndrome, a rare condition with an estimated incidence of 2-4 new cases per 100,000 each year. Relatively little is known about the role of endocytic trafficking in podocyte signaling and maintenance of the slit diaphragm integrity. This review will focus on the role of endocytic trafficking at the mature podocyte slit diaphragm.